Imperfektiv oder Perfektiv? Die Krux mit dem slavischen Verbalaspekt aus deutscher Sicht (am Beispiel des Polnischen) - Schwenk, Hans-Jörg (Glottodidactica, 2008)
The present paper deals with the category of aspect as it occurs in Slavic Languages in general and in Polisch in particular and the way it is treated by the authors of textbooks of Polish designed to serve the needs of non-native speakers whose mother tongue lacks the morphological distinction of perfective and imperfective verbs. Special attention is paid to teaching problems which arise from both the nature and the theory of aspect. It could be shown that teaching and learning strategies which aim at enhancing problem-solving skills in the field of aspect cannot be developed at all levels and independently of theoretical issues. The latter, however, as it seems, have to undergo a critical revision thus giving birth to valuable and reliable didactic concepts leading to more efficiency and more satisfying results.